Economic Value of a Beef Tenderness-Based Fed Cattle Valuation System - Schroeder, Ted C.; Riley, John Michael; Fraisier, Kelsey J. (Kansas State University. North American Institute for Beef Economic Research, 2010)
This study focuses on one component of the complex beef tenderness arena - - developing a meat tenderness valuation system for fed cattle. Development of a tenderness premium and discount schedule for fed cattle will provide increased incentive for producers to adopt animal genetic and production strategies that improve beef tenderness.
Keywords: Beef; Beef tenderness; Steak; Consumer demand